THE PRINCIPLE OF HONESTY IN THE FIRE INSURANCE AGREEMENT IN INDONESIA IN REALIZING A LEGAL BALANCE FOR THE PARTIES - SIREGAR, LUKMAN (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
Insurance under the Law of the Republic of Indonesia Number 2 of 1992 concerning Insurance Business Chapter 1, Article 1: